Analisis Framing CNN Indonesia terhadap Figur Purbaya: Representasi Teknopolitik dalam Pemberitaan Ekonomi Nasional (10 September–6 November 2025) - Muh. Aswad; Muliadi Mau; Ahmad Ismail (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze CNN Indonesia's framing of the figure of Purbaya Yudhi Sadewa in national economic news during the period of September 10-November 6, 2025, as well as reveal the technopolitical values represented through the construction of the media. The approach used is qualitative descriptive with the framing analysis method of Robert N. Entman (1993), which includes four dimensions: define problems, diagnose causes, make moral judgment, and suggest remedies. The data was obtained from CNN Indonesia's news on economic channels and analyzed by linking the theory of Representation (Stuart Hall, 1997), Technopolitics (Andrew Feenberg, 1999), and Media Political Economy (Vincent Mosco, 2009) as an interpretive framework. The results of the study show that CNN Indonesia frames Purbaya as a rational, professional, and scientific technocrat figure who plays a role in maintaining national economic stability. Through this framing, the media forms the image of Purbaya as a symbol of economic policy credibility and government legitimacy, by prioritizing objective narratives and depoliticizing economic issues. The analysis of representation reveals that the media uses symbols, language, and digital technology to create an image of technocracy that is integrated with power, while the media's approach to political economy shows that the news is inseparable from the ownership structure and market orientation that play a role in determining the direction of national economic discourse. The conclusion of this study is that CNN Indonesia's coverage of the figure of Purbaya reflects symbolic technopolitical practices, where power, technology, and scientific rationality combine to form the legitimacy of the government's economic policies. The implications of this study confirm the importance of the role of the media in maintaining a balance between the objectivity of news and the critical responsibility for power, so that the media continues to function as a reflective and democratic public spaceKeywords: Framing, CNN Indonesia, Purbaya Yudhi Sadewa, Technopolitics, Political Economy of the Media.